Personality In Terry Mccaleb, The Major Character Of Blood Work Movie: A Psychoanalitic Approach - Arifin, Khoirudin Listiawan, Drs. Abdillah Nugroho, M. Hum, Dr. Anam Sutopo, M.Hum (2014)
The problem of the study is the past trauma focused on the major character namely Terry McCaleb and the structural elements in Brian's Blood Work. This study is a qualitative study. The research uses two data sources, namely primary data source and secondary data source. The primary data source is the data taken from the text of Blood Work by Brian Helgeland. The secondary data source is other sources related to the analysis such as the author biography, books about the psychology, particularly related to the psychoanalytic theory of Sigmund Freud, and internet. The method of collecting data is done through documentation or library research. The techniques of data analysis are taking note the data, arranging the data, and describing the data based on psychoanalytic theory. Based on the analysis, the researcher draws conclusion. Blood Work movie explains that the major character in the movie is so traumatic. He is a FBI agent who had a heart attack when he tried to catch the killer before retirement. Since the tragedy, he has shut down and shut him self off from the world. He lives in a quiet life and restores the boat on which he lives in Los Angeles Harbor. When Graciela Rivers asked him to investigate her sister's death, Gloria's, her story hooked him immediately, the past trauma drives him to suicide. The main character, Terry McCaleb shows the act of past trauma. He is willing to leave his memory on the tragedy by finding the killer. He experienced intense emotion and reactivity (mostly anger and anxiety), flashback, and numbness. Those are emotional reactions.